The Effect Of The Show-and-Tell Learning Model On First-Grade Elementary School Students’ Interest In Learning And Speaking Skills - Ratna Juita; Sucipto; Muhajir (Celebes Journal of Elementary Education, 2026)
Learning the Indonesian language in elementary education is crucial for enhancing students' communication abilities, motivating them to learn, and improving their speaking skills. This research aimed to investigate the influence of the Show-and-Tell educational model on first-grade students' interest in learning and their speaking proficiency at UPTD SDN Kemayoran 1 Bangkalan. A quantitative experimental approach was utilized, which included both control and experimental groups. Data collection was carried out using observation checklists and performance evaluations, then analyzed with an independent samples t-test and MANOVA. Results indicated that the students who experienced the Show-and-Tell approach had higher average scores in their learning interest (M = 23.97) than those in the traditional model (M = 15.21), revealing a notable difference (p < 0.001). Likewise, the experimental group demonstrated superior speaking abilities (M = 15.56) compared to the control group (M = 7.50), also indicating significant differences (p < 0.001). The results from MANOVA also confirmed that the Show-and-Tell approach had a significant impact on both learning interest and speaking skills together. To sum up, the Show-and-Tell educational model can serve as an effective strategy focused on students to enhance their motivation and communication skills in primary education. Future research is encouraged to include more participants and a longer duration of intervention